Legal Issues Behind Village Autonomy and Village Head Role in Village Governments - Anggun Rahmawati; Arief Budiono; Syaifuddin Zuhdi; Nuria Siswi Enggarani (Audito Comparative Law Journal (ACLJ), 2023)
The village government is currently given lots of new authority and funding from both the central and regional governments. Such things aim to increase the progress of development and prosperity of village communities. Unfortunately, this does not necessarily make the village governments run according to existing laws. Worse, they do not necessarily make progress. Concerning the prosperity of villagers, since the enactment of Law Number 22 of 1999, major changes have happened to villages. They are no longer areas that are directly supervised by the regional government or merely administrative areas. But the village has transformed into an independent and separate autonomous force with the peculiarities of self-government. This paper uses the normative juridical research method. Results show that the lengthy tenure of village heads impacts the democratization process in the regions. It will result in the stagnation of development progress in the villages. These conditions certainly resulted in negative speculations about the consequences arising from violations of justice to the possibility of many legal violations due to the long Village Head office term